دور المخابر العلمية في تنمية المهارات البحثية لدى طلبة الدكتوراه - منصور, لندة; بن عيسى, رابح (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة الحالية إلى: محاولة التعرف على دور مخابر البحث العلمية في تنمية مهارات البحث لدى طلبة الدكتوراه وذلك من خلال الكشف عن دور النشاطات التي تنظمها هذه المخابر العلمية وكيف تساهم في تنمية المهارات البحثية لطلبة دكتوراه ألمدي علوم اجتماعية، استخدامنا المنهج الوصفي التحليلي، وطبقنا أداة منهجية تمثلت في المقابلة المقننة، حيث أجريت هذه الدراسة على عينة مكونة من (15) طالب وطالبة والمسجلين في دكتوراه ألمدي علوم اجتماعية بجامعة الشهيد حمه لخضر-الوادي-خلال السنة الجامعية 2020-2021، وقد توصلت إلى النتائج التالية، أن الدورات التكوينية، والملتقيات، والندوات، والتظاهرات العلمية التي تنظمها مخابر البحث العلمية تساهم بشكل كبير في تنمية المهارات البحثية لدى طلبة دكتوراهألمدي علوم اجتماعية، خاصة في إعداد الأطروحة، في حين نقص الإمكانات المادية من معدات، وأجهزة ووسائل تكنولوجية حديثة في هذه المخابر البحثية ومن توصيات هذه الدراسة، يجب توفير كافة الإمكانيات المادية، والتدريب التقني من خلال التركيز على الجانب العملي التطبيقي، وإنشاء فرقة بحثية متفرغة للاستشارات البحثية، بهدف تنمية الموارد البشرية، وتطوير البحث العلمي والأكاديمي. Abstract: The current study aims to, an attempt to identify the role of scientific research laboratories in developing research skills of doctoral students by uncovering the role of activities organized by these scientific laboratories and how they contribute to the development of research skills for PhD LMD students in Social Sciences. A methodology represented in the descriptive analytical method, as this study was conducted on a sample of (15) male and female students enrolled in the LMD PhD in Social Sciences at El-Qued University - during the academic year 2020-2021, and it reached the following results. The training courses, forums, seminars, and scientific events organized by the scientific research laboratories contribute greatly to developing the research skills for PhD LMD students in social sciences, especially in preparing the thesis, while the material capabilities of modern technological equipment, devices and means are lacking in these research laboratories. Among the recommendations of this study, all material capabilities and technical training must Bo provided by focusing on the practical, applied aspect, and establishing a dedicated research team for research consultations, with the aim of developing human resources and developing scientific and academic research.
مقال
Keywords: المخابر العلمية ; مهارات البحث العلمي ; طالب دكتوراه; Scientific laboratories, Scientific research skills, doctoral student